A case of cardiac calcified amorphous tumor (cardiac CAT) causing acute embolism in right common iliac artery. Issue 3 (March 2015) - Nakashima, Yasuteru; Terauchi, Yasunobu; Noguchi, Tatsuya; Tanioka, Katsutoshi; Kubo, Toru; Yamasaki, Naohito; Kitaoka, Hiroaki
Abstract A 68-year-old man was admitted to our hospital for the further examination of intermittent claudication. He had been on continuous ambulatory peritoneal dialysis for 2 years. Screening transthoracic echocardiography (TTE) revealed a club-shaped tumor and a round-shaped tumor attached to mitral annulus calcification (MAC). The club-shaped tumor was swinging and plunged into the left ventricle at diastolic phase. Because of the risk of fatal embolism, we planned early surgical resection of the tumors. However, 13 days after admission, his intermittent claudication was getting worse and some part of the club-shaped tumor had vanished by TTE. Urgent iliac angiography showed that the tumor had embolized the right common iliac artery. Although we tried embolectomy using a Fogarty catheter, it was unsuccessful. We therefore treated the iliac artery stenosis by endovascular therapy and the procedure was successful. Three months later, he suffered from unstable angina and was treated by percutaneous coronary intervention. However, subacute stent thrombosis occurred after one month. After urgent treatment, we decided to treat him by coronary artery bypass graft and surgical resection of the residual tumor on MAC. The operation was performed successfully. Finally, the tumor was diagnosed as cardiac calcified amorphous tumor by its histologic features. <Learning objective: Cardiac calcified amorphous tumor (CAT) is a rare, non-neoplastic cardiac tumor. Mobile and pedunculated cardiac CAT is considered to be an important risk of systemic embolism. Based on our case and previous reports we reviewed cardiac CAT, especially MAC-related CAT, and it appears to be related to end-stage renal disease and may grow within a short duration. It is important to perform routine serial echocardiography for hemodialyzed patients in whom MAC has been identified.>